Australia 1:250 000 bathymetric survey Sheet SE 50-11. - Australia. Division of National Mapping ([Canberra] : NATMAP, 1981)
Relief shown by bathymetric tints and bathymetric isolines.
Some sheets show soundings and bathymetric isolines on verso.
Keywords: Indian Ocean -- Maps; Bathymetric maps